MEKANISME KUN FAYAKUN QS. YASIN: 82 DALAM PERBUATAN TUHAN DAN MANUSIA (TEOSENTRIS DAN ANTROPOSENTRIS) - Leni Marlina; Komarudin Sassi (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to analyze the mechanism of kun fayakūn in QS. Yasin: 82 in the deeds of God and humans through theocentric and anthropocentric perspectives and its relevance to meaningful learning in Islamic education. This study uses the maudhū‘ī interpretation method with theological, philosophical, and pedagogical approaches within the framework of library research. The results of the study show three main findings. First, kun fayakūn in God's deeds is a manifestation of the absolute will and power of Allah SWT in creating and regulating all reality. Second, kun fayakūn in human actions is reflected in the endeavor, creativity, and utilization of potential bestowed by Allah so that humans play a role as active subjects in realizing their life goals. Third, the values ​​of kun fayakūn have strong relevance in the formation of adaptive character in the digital era through meaningful learning. These values ​​are able to foster optimism, independence, creativity, responsibility, and resilience in facing social change and current technological developments.